A Camp for the New Boston Cooperative: Cuyler, New York - Russell Hamlet (Oz, 1986)
The New Boston Cooperative is an association of farmers, homesteaders and fellow travelers founded in the 1930's as a last ditch-attempt to reserve the traditional rural lifestyle of the region. Today members are well-educated refugees from the cities and suburbs with the same central purposes...